Swine manure dilution with lagoon effluent impact on odor reduction and manure digestion. Issue 2 (2nd March 2021) - Hwang, Okhwa; Scoggin, Kenwood; Andersen, Daniel; Ro, Kyoung; Trabue, Steven
Abstract: Manure management systems have a major impact on odor from swine operations. A study was conducted to compare deep‐pit manure management systems to flushing barn manure management systems for odor reduction and organic matter degradation. Bioreactors were used to mimic manure management systems in which manure and lagoon effluent were loaded initially, and subsequent manure was added daily at 5% of its storage capacity (1 L). Final manure‐to‐lagoon effluent ratios were 10:0 (deep‐pit manure management system), 7:3 (Korean flushing systems), 5:5 (enhanced flushing systems), and 2:8 (enhanced flushing systems). At the end of the trial, at 4 (2:8), 10 (5:5), or 14 (10:0, 7:3) d, manure and gas concentrations of odorants were measured, including total solids (TS), total N (TN), and total C (TC) of manure. Odor was evaluated using the odor activity values (OAVs), and regression analysis was used to determine the effects of dilution and TS on manure properties and OAVs. Solids in the manure were positively correlated to TN, TC, straight chain fatty acids (SCFAs), branch chain fatty acids (BCFAs), total phenols, and total indoles and positively correlated to OAV for SCFAs, BCFAs, ammonia, total phenols, and total indoles. Reducing TS by 90% reduced BCFA, ammonia, phenols, and indoles by equal amounts in air. Carbon dioxide was the main C source evolved, averaging over 90%, and CH4 increased with dilution quadratically. Overall, reducing solids in manure by dilution had the biggest impact on reducing odor and increasing organic C degradation. Core Ideas: Manure odor was significantly reduced with solids removal. Solids in manure were correlated to protein‐derived odorants. Dilution of manure increased manure degradation rates. Manure solids are a good surrogate for odor emissions. Methane production increased quadratically with dilution.